Religion, redemption and revolution : the new speech thinking of Franz Rosenzweig and Eugen Rosenstock-Huessy - Cristaudo, Wayne, 1954- (University of Toronto Press, 2012)
"Religion, Redemption, and Revolution closely examines the intertwined intellectual development of one of the most important Jewish thinkers of the twentieth century, Franz Rosenzweig, and his friend and teacher, Christian sociologist Eugen Rosenstock-Huessy. The first major English work on Rosenstock-Huessy, it also provides a significant reinterpretation of Rosenzweig's writings based on the thinkers' shared insights - including their critique of modern Western philosophy, and their novel conception of speech.